Long-term suppression of severe recurrent genital herpes simplex infections with oral acyclovir: a dose-titration study. Issue 2 (April 1990) - Kroon, S; Petersen, C S; Andersen, L P; Rasmussen, J R; Vestergaard, B F
Abstract : Twenty immunocompetent patients, four females and 16 males, with severe recurrent genital herpes (median number of recurrences the previous year 16, range (8-24] entered an open continuous long-term suppressive treatment with oral acyclovir (ACV) for 12 months. The study included a dose-titration schedule: (ACV, 200 mg x 4/1-3 months, ACV, 400 mg x 2/4-6 months, ACV, 200 mg x 2/7-9 months, and ACV, 400 mg x 1/10-12 months). Patients with recurrences on steps two and three received an alternative dose of ACV, 200 mg x 3. Otherwise patients entered the previous dose-step. Five (20%) of patients were completely free of symptoms (recurrences and abortive lesions) during the four dose-reduction periods. A further nine patients (50%) could be dose-reduced to 200 mg x 3 without symptoms. Isolates from three patients showed a decrease in virus sensitivity after ceasing treatment. In conclusion, 14/20 of treated patients could be dose reduced to 200 mg x 2-3 without selection of HSV strains showing clinically important decreases in sensitivity towards ACV.